Hybrid real time simulator application for active adaptive control systems design and testing tasks; Liberalization and modernization of power systems: smart technologies for joint operation of power grids - Borovikov Y. S. Yuri Sergeevich (2012, 2012)
В фонде НТБ ТПУ отсутствует